Mengembalikan Pendidikan Anak Usia Dini di Rumah Sebagai Bentuk Tanggung Jawab Orang Tua Selama Pandemi - Shintike Maya; Talizaro Tafonao (CARAKA: Jurnal Teologi Biblika dan Praktika, 2021)
The purpose of writing this article is to see the effectiveness of learning since home-centered education during the pandemic. Before the pandemic, education at home was not an urgent matter for families, but with the presence of this covid-19, now the home has become the most appropriate place to teach Christian Religious Education repeatedly for early childhood children in learning, with various efforts and challenges faced by parents as described in this article. The method used is a qualitative descriptive method by examining the learning process at home based on Deuteronomy 6:6-9 during a pandemic. The analysis process is carried out using Bible verses in the Book of Deuteronomy and various other sources of literature such as journals, books, and other reliable reference materials related to this study. The results found by the authors that the nature of early childhood education is a concern for parents during the pandemic by looking at the concept of education in the Deuteronomy, namely parents as the main teacher / mentor, training, providing materials, examples and time. Thus, the family environment is the main environment in the formation of all aspects of early childhood life during the pandemic.